Zero-one law for (a,k)-regularized resolvent families and the Blackstock-Crighton-Westervelt equation on Banach spaces - Gambera, Laura Rezzieri [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
This work presents some results of the theory of the (a,k)-regularized resolvent families, that are the main tool used in this thesis. Related with this families, one result proved in this work is the zero-one law, providing new insights on the structural properties of the theory of (a,k)-regularized resolvent families including strongly continuous semigroups, strongly continuous cosine families, integrated semigroups, among others. Moreover, an abstract nonlinear degenerate hyperbolic equation is considered, that includes the semilinear Blackstock-Crighton-Westervelt equation. By proposing a new approach based on strongly continuous semigroups and resolvent families of operators, it is proved an explicit representation of the strong and mild solutions for the linearized model by means of a kind of variation of parameters formula. In addition, under nonlocal initial conditions, a mild solution of the nonlinear equation is established.

Este trabajo presenta algunos resultados de la teoría de las familias resolventes (a,k)-regularizadas, que es la principal herramienta utilizada en esta tesis. Relacionado con estas familias, uno de los resultados demostrados en este trabajo es la ley cero-uno, proveyendo nuevas percepciones de propiedades estructurales de la teoría de las familias resolventes (a,k)-regularizdas, incluyendo los semigrupos fuertemente continuos, las familias coseno fuertemente continuas, los semigrupos integrados, entre otras. Además, una ecuación degenerada no lineal abstracta es considerada, la cual incluye la ecuación semilineal de Blackstock-Crighton-Westervelt. Proponiendo un nuevo enfoque basado en semigrupos fuertemente continuos y familias resolvente, es demostrada una representación explícita de las soluciones fuerte y débil de la linealización del modelo por una especie de método de variación de parámetros. Por fin, bajo condiciones iniciales no locales, una solucion débil de la ecuación no lineal es establecida.

Este trabalho apresenta alguns resultados da teoria de famílias resolventes (a,k)- regularizadas, que é a principal ferramenta utilizada nesta tese. Relacionado com estas famílias, um resultado provado neste trabalho é a lei zero-um, que fornece novas percepções de propriedades estruturais da teoria de famílias resolventes (a,k)- regularizadas, incluindo os semigrupos fortemente contínuos, as famílias cosseno fortemente contínuas, os semigrupos integrados, entre outras. Além disso, uma equação hiperbólica degenerada não-linear abstrata é considerada, a qual inclui a equação semilinear de Blackstock-Crighton-Westervelt. Propondo uma nova abordagem baseada em semigrupos fortemente contínuos e famílias resolvente, é demonstrada uma representação explícita das soluções forte e branda para a linearização do modelo por uma espécie de método de variação dos parâmetros. Por fim, sob condições iniciais não-locais, uma solução branda da equação não-linear é estabelecida.
Lei zero-um para famílias resolvente (a,k)-regularizadas e a equação de Blackstock-Crighton-Westervelt em espaços de Banach
Keywords: (a,k)-regularized resolvent families; Zero-one law; Blackstock-Crighton-Westervelt equation; Well-posedness; Ley cero-uno; Equación de Blackstock-Crighton-Westervelt; Buen planteamiento; Famílias resolvente (a,k)-regularizadas; Lei zero-um; Equação de Blackstock-Crighton-Westervelt; Boa colocação